Natural Capital, Ecosystem Services, and Environmental Accounting - Manes, Fausto; Buonocore, Elvira; Paletto, Alessandro; Franzese, Pier Paolo (Journal of Environmental Accounting and Management, 2026)
Natural capital stocks generate ecosystem services flows that are directly used or enjoyed by people, providing benefits to human well-being. Anthropogenic pressures on natural ecosystems cause biodiversity loss and, in turn, affect the capability of natural ecosystems to provide flows of good and services to humans. Environmental accounting represents a useful tool to assess the value of ecosystem goods and services, also providing useful information to local managers and policy makers in charge of implementing management and policy strategies oriented to the sustainable use of natural resources. Given this premise, this special issue includes theoretical, methodological, and applied papers focusing on natural capital, ecosystem services, and environmental accounting.